Microsoft Project : covering Project Online Desktop Client - Lewis, Cindy M. (Cindy Marie) (Step by step, 2021)
The quick way to learn Microsoft Project! This is learning made easy. Get more done quickly with Microsoft Project. Jump in wherever you need answers brisk lessons and detailed screenshots show you exactly what to do, step by step. Quickly start a new plan, build task lists, and assign resources Share your plan and track your progress Capture and fine-tune work and cost details Use Gantt charts and other views and reports to visualize project schedules Share resources across multiple plans and consolidate projects Manage Agile plans using the new task boards to create backlogs, plan sprints, and hold scrum meetings Learn more about integrating Project with Microsoft 365 solutions for collaboration Master project management best practices as you learn Project Easily identify the features and lessons you need.